Modeling the Inflation Rates in Syria Using the TGARCH Model for the period 2016-2021 - شفيق اسماعيل, رولى; أحمد أديب أحمد , (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This research aims to study the impact of shocks on the fluctuations of a series of inflation rates in order to reach a significant standard model that measures these fluctuations for the period 2016-2021. The descriptive analytical approach was adopted in describing and analyzing the studied series of inflation rates, which is a monthly series starting from January 2017 and it ends in December 2021, taken from the Syrian statistical collections for the years 2017 to 2022. We used TGARCH model with asymmetric thresholds to study fluctuations in the series of inflation rates. The research concluded that the monthly series of inflation rates is stable at the first difference, with fluctuations starting from the beginning of 2020. After the comparison between the models we decided that the ARIMA (0,1,1) model is the model which generate the series, and that the TGARCH model (1,1) is the model that generates fluctuations, and this confirms the presence of an effect of shocks on the fluctuations of the series of inflation rates, but there is no symmetry for the effect of negative and positive shocks on these fluctuations.